ORGANIZATIONAL AND ECONOMIC MECHANISM FOR POST-WAR DEVELOPMENT OF THE NATIONAL ECONOMY: GOVERNANCE LOOP AND IMPLEMENTATION CRITERIA - Matvievsky, Nazar (Public Management and Policy, 2026)
The paper develops a governance-oriented design of an organizational and economic mechanism for post-war development of the national economy. The problem addressed is the fragmentation of recovery programmes when goals, resources, instruments and accountability are not linked through measurable control indicators, which reduces the reproducibility of policy decisions across sectors and regions. The purpose of the study is to translate the mechanism from a conceptual description into an implementation-ready model by representing it as a management loop with explicit inputs, policy instruments, expected outputs, control metrics and responsible actors. The methodology combines structural-functional modelling, process decomposition and a project-and-portfolio perspective on recovery interventions. As a result, a matrix of the management loop is proposed using the logic “input parameters – instrument of influence – expected result – control indicator – responsible subject”. The matrix allows aligning project prioritisation, medium-term budgeting, donor schedule coordination, regulatory simplification, contractor capacity management and digital monitoring with audit procedures and public accountability. In addition, the paper systematises the coordinating functions of the state in post-war transformation and formulates implementation criteria that define minimum launch preconditions, institutional ownership, time horizons, key risks and mitigation controls. The practical value of the findings is the ability to embed the mechanism into recovery programmes and project portfolios, set transparent KPIs, organise feedback loops and adjust instruments based on observed performance, thereby increasing policy coherence and delivery quality. The model is applicable for combining public investment, donor resources and public-private partnerships, while keeping social and human-capital measures within the same results chain. It also supports the creation of a unified information space for recovery, where open data on costs, progress and risks enable continuous learning and prevent duplication of mandates among coordinating bodies.